2021
DOI: 10.1029/2021tc006791
|View full text |Cite
|
Sign up to set email alerts
|

On the Rootless Nature of a Devonian Suture in SW Iberia (Ossa‐Morena Complex, Variscan Orogen): Geometry and Kinematics of the Azuaga Fault

Abstract: Recognizing the major architecture of a collisional orogen relies on an understanding of its suture zone(s). The final structure and local geometry of a suture zone is typically the result of multiple deformation events, from the subduction that records convergence to the syncollisional and postcollisional structures responsible for the lithospheric thickening and/or thinning that follow (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(50 citation statements)
references
References 106 publications
(97 reference statements)
6
39
5
Order By: Relevance
“…Actually, most of the stereoplots presented by Díez Fernández et al. (2021) in their Figure 7 are incongruent with the inferred sizes and rounded geometries of the hinge zones, since S 2 orientation shows a bimodal distribution that denotes dominant moderate to steep dips, with almost no subhorizontal dips.…”
Section: Geometry Of the Late‐metamorphic Folds Affecting The Central...mentioning
confidence: 82%
See 4 more Smart Citations
“…Actually, most of the stereoplots presented by Díez Fernández et al. (2021) in their Figure 7 are incongruent with the inferred sizes and rounded geometries of the hinge zones, since S 2 orientation shows a bimodal distribution that denotes dominant moderate to steep dips, with almost no subhorizontal dips.…”
Section: Geometry Of the Late‐metamorphic Folds Affecting The Central...mentioning
confidence: 82%
“…A mylonitic deformation affected the whole central unit and gave way to a penetrative planar-linear tectonic fabric (S 2 in Díez Fernández et al, 2021), which is the structural feature more commonly observed and measured in the field (Azor et al, 1994;Burg et al, 1981;Pereira et al, 2008). Díez Fernández et al (2021) mistakenly attribute the "earlier exhumation from eclogite facies conditions to the lower-middle crust" to this mylonitic fabric. Actually, this deformation occurred at variable conditions from high-temperature (sillimanite zone) at the lower part of the unit to low-grade ones at the upper part (garnet-biotite zone), and has been interpreted as related to the exhumation of the unit up to upper crustal levels (Azor, 1994;Azor et al, 1994).…”
Section: Geometry Of the Late-metamorphic Folds Affecting The Central...mentioning
confidence: 99%
See 3 more Smart Citations